2020
DOI: 10.1002/pds.4968
|View full text |Cite
|
Sign up to set email alerts
|

Do drug‐related safety warnings have the expected impact on drug therapy? A systematic review

Abstract: Purpose The need for drug‐related safety warnings is undisputed, and their impact should also be evaluated. This systematic review investigates and assesses the impact of safety warnings on drug therapy. Methods Studies published in English between January 1998 and December 2018 were searched in EMBASE and MEDLINE, complemented by manual search. Randomised controlled trials, cohort studies with a before/after component, and case‐control studies were included, selected to predefined criteria, and assessed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…Written safety warnings on human drugs addressed to health care professionals (e.g., physicians and pharmacists) intend to minimise the risk of drug therapy. The need for drug-related safety warnings is therefore undisputed and three systematic reviews [1][2][3] investigated their impact on prescribing behaviour. Many studies included in these reviews described the impact of safety warnings contradictorily.…”
Section: Introductionmentioning
confidence: 99%
“…Written safety warnings on human drugs addressed to health care professionals (e.g., physicians and pharmacists) intend to minimise the risk of drug therapy. The need for drug-related safety warnings is therefore undisputed and three systematic reviews [1][2][3] investigated their impact on prescribing behaviour. Many studies included in these reviews described the impact of safety warnings contradictorily.…”
Section: Introductionmentioning
confidence: 99%
“…Current research on the effectiveness of advisories is mixed and has mostly focused on individual advisories and regulators. There have been a small number of systematic reviews which have investigated the effects of these advisories on rates of prescribing 38‐42 . These have generally found that the current evidence is mixed, as advisories may have intended or unintended effects, to varying degrees, emphasizing that more research is required to understand why these effects are seen.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] These have generally found that the current evidence is mixed, as advisories may have intended or unintended effects, to varying degrees, emphasizing that more research is required to understand why these effects are seen. One review which looked into papers on FDA advisories found that there was a mixed impact depending on the type of advisory 38.…”
mentioning
confidence: 99%
“…5 Systematic reviews suggest advisories issued by regulators may influence clinical practice. [6][7][8][9] Original research with a recommendation to change practice based on a change or restriction in indication were associated with a 34% change in the rate of prescribing in the intended direction, while risk communications to 'be aware' of new information about a drug's risk were associated with an 11% change in prescribing. 9 These findings suggest prescribing changes may differ in relation to how information about drug risk is communicated in an advisory.…”
Section: Introductionmentioning
confidence: 99%